Civil Society Organizations' Experiences of Participative Environmental Mainstreaming: A Political Systems Perspective of a Regional European Polity. (20th July 2016) - Chaney, Paul
Abstract: This paper addresses a lacuna in the literature on environmental policy integration by exploring civil society organizations' (CSOs) experiences of participative environmental mainstreaming – a policy imperative to embed environmental concerns in all aspects of policy‐making. A raft of international treaties and laws require this to be operationalized through knowledge exchange and critical engagement between governing elites and exogenous groups. Findings reveal how CSOs' participation is shaped by electoral politics, party dynamics, veto players and strategic bridging. Respondents also questioned whether mainstreaming is more concerned with legitimation, performativity and the appearance of participative policy‐making than with outcomes. The wider contribution of the study is three‐fold: it reveals the issues and challenges facing CSOs, it underlines the need for adaptive engagement strategies and it shows the contingent nature of state attempts to foster civil society participation in environmental policy‐making. © 2016 The Authors Environmental Policy and Governance published by ERP Environment and John Wiley & Sons Ltd